Cytospora paraplurivora sp. nov. isolated from orchards with fruit tree decline syndrome in Ontario, Canada. - Evgeny Ilyukhin; Hai D T Nguyen; Alan J Castle; Walid Ellouze (PLoS ONE)
A new species of Cytospora was isolated from cankered wood of Prunus spp. during a survey of orchards exhibiting symptoms of fruit tree decline syndrome in southern Ontario, Canada. We found isolates that are morphologically similar to species in the Cytosporaceae family, which is characterized by single or labyrinthine locules, filamentous conidiophores or clavate to elongate obovoid asci and allantoid, hyaline conidia. Multi-gene phylogenetic analysis of ITS, LSU, act and tef1- α showed that the isolates form a distinct clade, sister to Cytospora plurivora. Morphologically, our isolates showed differences in the length of conidia and culture characteristics compared to C. plurivora, suggesting the establishment of a new species. The species is described as Cytospora paraplurivora sp. nov. and placed in the family Cytosporaceae of Diaporthales. Additionally, we sequenced, assembled and characterized the genome of the representative isolate for this new species. The phylogenomic analysis confirms the species order and family level classification. C. paraplurivora sp. nov. has the potential to severely affect stone fruits production, causing cankers and dieback in stressed trees, and eventually leads to tree decline. Pathogenicity tests show that the species is pathogenic to Prunus persica var. persica.